Abdurrahman Wahid’s Political Legacy and the Development of Civilisation Fiqh in Indonesia - Syafa'at, Abdul Kholiq; Fauzi, Moh Nur (De Jure: Jurnal Hukum dan Syari'ah, 2025)
This study examines the intersection between Abdurrahman Wahid’s concept of Cosmopolitan Fiqh and Nahdlatul Ulama’s recent initiative of Fiqh of Civilisation. This study seeks to analyse three primary aspects: Wahid’s cosmopolitan fiqh model, its epistemological construction, and its contribution to democracy in Indonesia. Wahid’s model of cosmopolitan fiqh is entrenched in a vision that positions fiqh not merely as a normative legal framework but as an instrument to promote universal humanity, protection of rights, and respect for diversity. The epistemological construction of this fiqh is shaped through a dialogical method, employing al-Jabiri’s trilogy of epistemology—bayani (textual reasoning), burhani (rational argument), and irfani (intuitive-cultural wisdom). This methodological approach enables the integration of Islamic teachings with Indonesia’s socio-political realities and indigenous wisdom, resulting in a flexible, context-sensitive fiqh. The findings reveal that Wahid’s cosmopolitan approach provides an epistemological foundation for the development of Fiqh of Civilisation within Nahdlatul Ulama. Its contribution to democracy in Indonesia is evident in three dimensions: strengthening democratic values and pluralism, ensuring the protection and recognition of rights across different groups, and projecting Indonesian Islam as a global model of peaceful and inclusive civilisation. Thus, Wahid’s fiqh serves as both a theoretical and practical reference for embedding Islamic principles within democratic and multicultural contexts.